(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2026)
This article analyzes religion as an instrument of politics and ideology in the international relations of the five post-Soviet states of Central Asia. The study examines how Kazakhstan, Uzbekistan, Kyrgyzstan, Tajikistan and Turkmenistan are instrumentalizing the religious factor to achieve foreign policy goals, strengthen the ideological foundations of power and international positioning in the context of globalization and transnational religious influences. Theoretically, the work is based on the concepts of religious diplomacy, «soft power» and securitization, demonstrating the transformation of religion from a marginalized element of the Soviet era into a multifunctional political and ideological resource. Across the region, religion is mobilized to legitimize power, construct national identity, justify authoritarian governance through security-centered discourses, and enhance symbolic capital in the international arena. A comparative perspective reveals distinct national models of religious instrumentalization. Kazakhstan employs interfaith dialogue as a soft-power mechanism and a means of strengthening international reputation. Uzbekistan leverages Islamic cultural heritage for diplomatic and economic benefit. Tajikistan uses religious regulation as an ideological rationale for authoritarian consolidation. Kyrgyzstan illustrates competition among political actors for influence over religious discourse. Turkmenistan incorporates religion into a personalized ideology that underpins isolationism. The article argues that these patterns are shaped by each state’s historical experience, regime type, ethno-religious composition, and geopolitical position. Key words: religion, politics, ideology, international relations, Central Asia, instrumentalization of religion, religious diplomacy, soft power, post-Soviet transformation.